RNA interference of Aspergillus flavus in response to Aspergillus flavus partitivirus 1 infection - Jiang, Yinhui; Liu, Xiang; Tian, Xun; Zhou, Jianhong; Wang, Qinrong; Wang, Bi; Yu, Wenfeng; Jiang, Yanping; Hsiang, Tom; Qi, Xiaolan (Frontiers in Microbiology, 2023)
RNA interference (RNAi) is one of the important defense responses against viral infection, but its mechanism and impact remain unclear in mycovirus infections. In our study, reverse genetics and virus-derived small RNA sequencing were used to show the antiviral responses of RNAi components in Aspergillus flavus infected with Aspergillus flavus partitivirus 1 (AfPV1). qRT-PCR revealed that AfPV1 infection induced the expression of the RNAi components in A. flavus compared with noninfected A. flavus. Knock mutants of each RNAi component were generated, but the mutants did not exhibit any obvious phenotypic changes compared with the A. flavus parental strain. However, after AfPV1 inoculation, production of AfPV1 was significantly less than in the parental strain. Furthermore, sporulation was greater in each AfPV1-infected mutant compared with the AfPV1-infected parental A. flavus. We also investigated the sensitivity of virus-free and AfPV1-infected RNAi mutants and the parental strain to cell wall stress, osmotic stress, genotoxic stress, and oxidative stress. The mutants of DCLs and AGOs infected by AfPV1 displayed more changes than RDRP mutants in response to the first three stresses. Small RNA sequencing analysis suggested that AfPV1 infection reduced the number of unique reads of sRNA in A. flavus, although there were many vsiRNA derived from the AfPV1 genome. GO term and KEGG pathway analyses revealed that the functions of sRNA affected by AfPV1 infection were closely related to vacuole production. These results provide a better understanding of the functional role of RNAi in the impact of AfPV1 on the hypovirulence of A. flavus.